Diaspora Start-Up Programs and Creative Industries: Evidence from Romania - Alin Croitoru (Transylvanian Review of Administrative Sciences, 2021)
Romania is one of the main countries of origin for intra-European migration. The national authorities recently implemented the first major program —Diaspora Start-up—to support the business initiatives of Romanian citizens who live abroad and who are interested in opening a business in their home country. This scheme was developed in parallel with a broader program—Romania Start-up Plus— which was designed to support the entrepreneurial initiatives of individuals residing inside the country. These programs have already supported over 8,600 non-agricultural start-ups created in urban areas. This study conducted a comparative analysis of the two programs based on different criteria and explored their regional dynamics regarding the emergence of start-ups and the prevalence of creative industries companies. The analysis highlighted important regional differences within Romania and revealed that the Diaspora Start-up program registered a statistically significant lower level of businesses registered as part of the creative industries. The results support the formulation of a hypothesis of negative selectivity within the programs designed to support Romanian migrants’ entrepreneurship, but further research is needed to test this hypothesis.